The role of banking service providers in customer satisfaction (Field study on private banks in Lattakia) - ماخوس, ديمة; سومر ناصر, (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The research aimed to clarify the role of banking service providers in customer satisfaction in private banks in Lattakia. The descriptive analytical method was used. Where the researcher relied on secondary data published in scientific and academic studies and research, reports issued by companies and on scientific research in this field. In order to test the hypotheses, the researcher dumped the raw data into a database that was analyzed using SPSS version /20/. The research community represented the clients of private banks in Lattakia Governorate. A soft sample was obtained. The researcher distributed the questionnaire to (233) clients from the research community, from which he retrieved (229) questionnaires, among which (13) were invalid for analysis, and thus the number of valid questionnaires for analysis is (216). The research reached a number of results, including: The role played by banking service providers in their technical, behavioral and personal characteristics in achieving customer satisfaction in private banks, and the existence of a statistically significant relationship between the technical skills of banking service providers and customer satisfaction in the banks under study, and this is reinforced by the explanatory value of R2, which amounted to (0.441), and the presence of A statistically significant relationship between the behavioral skills of banking service providers and customer satisfaction in the banks under study, and this is reinforced by the explanatory value of R2, which amounted to (0.555).